Structure and defect strategy towards high-performance copper niobate as anode for Li-ion batteries - Su, M.; Li, M.; He, K.; Wan, T.; Chen, X.; Zhou, Y.; Zhang, P.; Dou, A.; Xu, H.; Lu, Chunsheng; Wang, R.; Chu, D.; et al. (ELSEVIER SCIENCE SA, 2023)
In search for new anode materials with high-capacity, ultra-fast charging, and safety characteristics for lithium-ion batteries (LIBs), copper niobate (Cu0.1Nb1.9O4.85 nanorods and Cu0.1Nb1.9O4.85 nanoparticles) has been demonstrated through structure and defect engineering for the first time. The copper niobate material presents a dual-block shear ReO3 crystal structure with large lattice parameters and shallow-level oxygen vacancies. The structural and morphological features of Cu0.1Nb1.9O4.85 nanoparticles offer high structural stability, an open crystalline skeleton, and enhanced Li+-transfer kinetics. Significantly, DFT calculations demonstrate lower bandgap and Li adsorption/formation energies, leading to enhanced ion/electron conductivities of Cu0.1Nb1.9O4.85. In-situ XRD techniques reveal the high structural stability and good mechanic property of Cu0.1Nb1.9O4.85 nanoparticles. Consequently, Cu0.1Nb1.9O4.85 nanoparticles present significant pseudocapacitive behavior (as high as 90.3 % at 1.1 mV s−1) and outstanding electrochemical performances. The reversible capacity can reach 398 mAh g−1 at 0.1C. Cu0.1Nb1.9O4.85 nanoparticles also exhibit excellent cycle lifespan (capacity retention of 95.2 % over 250 cycles, 1C) and impressive rate performance (188 mAh g−1 at 20C and maintains 97.3 % upon 2500 cycles). Even at a high rate of 100C, it can still deliver a charge capacity of 45 mAh g−1. Moreover, the Cu0.1Nb1.9O4.85 nanoparticles‖LiNi1/3Co1/3Mn1/3O2 full cell delivers a capacity of 150.6 mAh g−1. These results reflect the huge application prospect of Cu0.1Nb1.9O4.85 nanoparticles for boosting Li+ storage.